Building green performance through green HRM and green transformational leadership: The mediation role of green innovation - Yuliza, Yuliza; Musa, Hendra (Asian Management and Business Review, 2025)
This study aims to analyze the effect of green human resource management (GHRM) and green transformational leadership on green performance with green innovation mediation. This study was conducted at start-up companies in the Yogyakarta area, involving 180 respondents. GHRM, green transformational leadership, green innovation, and green performance are measured using indicators adapted from previous research. The analysis shows that GHRM and green transformational leadership positively influence green performance. In addition, green innovation has been proven to mediate the relationship between GHRM and green transformational leadership and green performance. These findings make a new contribution to the literature by reinforcing the role of green innovation as a linking mechanism between GHRM policies and transformational leadership styles on corporate environmental performance. Proposed managerial implementations include strengthening GHRM practices and adopting green-based transformational leadership to encourage innovation and improve environmental performance. This research also allows further exploration of other variables that may influence this relationship.